A high-toughness conductive polypropylene sheet for power batteries and a method for preparing the same

CN122958792APending Publication Date: 2026-10-23SUNWAY PRECISION TECHNOLOGY (GUANGDONG) CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611135282.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0007]现有的导电聚丙烯片材在应用于动力电池包覆及漏液检测时,存在导电性与力学性能难以兼顾的问题

Benefits of technology

[0029](1)提升材料的导电性能

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a kind of high toughness conductive polypropylene sheet for power battery and preparation method thereof, it is related to high-performance polypropylene technical field.The application discloses high toughness conductive polypropylene sheet for power battery, including the following weight parts of raw materials: 60-75 weight parts polypropylene resin, 10-20 weight parts MAH-GMA co-grafting modified PP resin, 10-22 weight parts composite conductive filler, 1-2.8 weight parts crosslinking penetration aid, 5-12 weight parts toughening modifier, 2-5 weight parts compatilizer, 0.3-1 weight parts antioxidant, 0.5-1.5 weight parts lubricant.The polypropylene sheet prepared in the application gives consideration to electrical conductivity and mechanical property, is applied in the electrolyte leakage device of power battery, and has important engineering application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-performance polypropylene technology, specifically to a high-toughness conductive polypropylene sheet for power batteries and its preparation method. Background Technology

[0002] With the rapid development of the new energy vehicle industry, the safety of power batteries has received increasing attention. Among the many safety hazards, electrolyte leakage is a particularly insidious and dangerous type of failure. Power battery electrolytes are mainly composed of flammable organic solvents (such as dimethyl carbonate (DMC) and ethylene carbonate (EC)) and conductive lithium salts. Once a leak occurs, it can lead to battery performance degradation and internal short circuits, or even thermal runaway and fire or explosion. Therefore, the ability to detect electrolyte leaks in their early stages, when the leakage is minimal and has not yet spread, is a crucial factor in ensuring the safety of power batteries.

[0003] Currently, methods for detecting electrolyte leaks mainly include gas sensor detection, optical detection, impedance / capacitance sensing, and resistive detection. Among these, resistive detection has become a key technology route for industry development due to its advantages such as simple structure, controllable cost, and ease of fault location. For example, patent application CN117664462A discloses a battery leak detection device. This device includes a leak detection strip arranged inside the battery casing, which is composed of a conductive material and an insulating layer. When electrolyte leakage occurs in the battery cell assembly, the leaked electrolyte acts as a conductive medium, creating a conductive path between the conductive material inside the detection strip and the battery casing. The leak detection unit determines whether a leak has occurred by detecting the change in resistance between the two, and can further deduce the location of the leak by analyzing the resistance value. This method can detect minute leaks before a large amount of electrolyte has flowed out of the battery casing, significantly improving sensitivity and location capabilities compared to traditional methods. However, this patented solution still faces a significant technical bottleneck in practical applications: the specific structure and material composition of the leakage detection strip have not been fully optimized, especially the lack of a polymer sheet with both good conductivity and excellent mechanical properties to meet the adaptation requirements of complex working conditions such as material stretching, bending and installation in the battery packing process.

[0004] Polypropylene (PP) is an ideal matrix for battery packing materials due to its excellent chemical resistance, good processing performance, and low cost. To enable PP to conduct electricity, existing technologies typically involve adding conductive fillers (such as conductive carbon black, carbon nanotubes, graphene, or conductive polymers) to the PP matrix and then melt-blending them to produce conductive polypropylene sheets. However, existing conductive polypropylene sheets have the following technical defects when used in power battery packing and leakage detection: (1) There is a prominent contradiction between conductivity and mechanical properties: To achieve the ideal conductivity effect (such as surface resistance <10 Ω·cm), 6 Ω), usually a large amount of conductive filler (such as conductive carbon black, the amount of which often exceeds 15%-20%). High filler content leads to a sharp decrease in the impact toughness of the PP matrix, the sheet becomes brittle, and it is very easy to break during bending or processing, which is far from meeting the requirements for stretching and forming during battery packing; (2) The conductive layer is easy to fall off: some existing technologies use multi-layer composite or surface coating, that is, to coat the surface of the PP sheet with a conductive coating to reduce the amount of filler. However, the bonding force between the conductive layer and the matrix of this structure is limited. Under humid and hot environment, long-term vibration or repeated bending conditions, the surface conductive coating is easy to wear or fall off, resulting in failure of conductive function; (3) The conductive filler is not evenly dispersed: nanoscale conductive materials (such as carbon nanotubes, graphene) are very easy to agglomerate in the PP matrix, and it is difficult to achieve uniform dispersion. There are problems such as local non-conductivity and unstable resistivity of the sheet; (4) Poor resistivity adjustability: once the formula and production process are fixed, the resistivity of the final product is basically locked. It is difficult to flexibly adjust the resistivity under the same production system to meet the needs of different application scenarios, such as antistatic grade (surface resistance 10 6 -10 9 Ω) and conductive level (surface resistance less than 10 6 Switching between Ω and other Ω often requires readjusting the formula and process, increasing production costs and time.

[0005] In conclusion, developing a conductive polypropylene sheet that combines high conductivity and excellent mechanical properties has significant engineering application value. Summary of the Invention

[0006] The purpose of this invention is to provide a high-toughness conductive polypropylene sheet for power batteries and its preparation method, thereby solving the following technical problems:

[0007] When existing conductive polypropylene sheets are used for power battery packs and leakage detection, there is a problem that it is difficult to balance conductivity and mechanical properties.

[0008] The objective of this invention can be achieved through the following technical solutions:

[0009] A high-toughness conductive polypropylene sheet for power batteries, comprising the following raw materials in parts by weight: 60-75 parts by weight of polypropylene resin, 10-20 parts by weight of MAH-GMA co-grafted modified PP resin, 10-22 parts by weight of composite conductive filler, 1-2.8 parts by weight of crosslinking and penetration promoter, 5-12 parts by weight of toughening modifier, 2-5 parts by weight of compatibilizer, 0.3-1 parts by weight of antioxidant, and 0.5-1.5 parts by weight of lubricant;

[0010] The preparation method of composite conductive filler includes the following steps:

[0011] A1: Add conductive carbon filler and ethanol solution to a reaction flask for dispersion, add glacial acetic acid to adjust pH to 4-5, add KH550 for dispersion, control the temperature at 60-70℃ and keep the reaction at this temperature for 2-4 hours, filter, wash and dry to obtain aminated modified carbon filler.

[0012] A2: Aminated modified carbon filler and anhydrous ethanol were added to a reaction flask for dispersion, triethylamine was added for dispersion, epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid was added, the temperature was controlled at 70-80℃ and the reaction was kept at this temperature for 1-2 hours, centrifuged, washed and dried to obtain the intermediate;

[0013] A3: Add the intermediate, Tris-HCl buffer, and anhydrous ethanol to the reaction flask for dispersion, add dopamine hydrochloride, and stir the reaction at room temperature for 2-4 hours; add tetraethyl orthosilicate for dispersion, adjust the pH to 8-9, control the temperature at 40-60℃, and keep the reaction at this temperature for 6-12 hours. Centrifuge, wash, and dry to obtain the composite conductive filler.

[0014] As a further aspect of the present invention: the crosslinking penetration enhancer is composed of dicumyl peroxide and triallyl isocyanurate in a mass ratio of 0.2-0.8:0.8-2;

[0015] The toughening modifier is POE-g-MAH or SEBS-g-MAH;

[0016] The compatibilizer is PP-g-MAH compatibilizer;

[0017] The antioxidant is composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 1-2:1;

[0018] The lubricant is calcium stearate.

[0019] As a further aspect of the present invention: the ethanol solution in A1 is composed of anhydrous ethanol and deionized water in a volume ratio of 9:1; the conductive carbon filler is composed of conductive carbon black and carbon nanotubes in a mass ratio of 3-5:1; the addition ratio of KH550, ethanol solution and conductive carbon filler is 4-8g:80-120mL:10g.

[0020] As a further aspect of the present invention: the addition ratio of aminated modified carbon filler, anhydrous ethanol, triethylamine, and epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid in A2 is 10g: 80-120mL: 0.2-0.5g: 0.4-1g.

[0021] As a further embodiment of the present invention: the amounts of intermediate, Tris-HCl buffer, anhydrous ethanol, dopamine hydrochloride, and tetraethyl orthosilicate added in A3 are 10g: 150-250mL: 40-80mL: 0.5-1.5g: 0.5-2mL.

[0022] As a further aspect of the present invention, the preparation method of MAH-GMA co-grafted modified PP resin includes the following steps: polypropylene resin, maleic anhydride, glycidyl methacrylate, styrene, and dicumyl peroxide are blended and fed into a twin-screw extruder, and extruded and granulated at 175-190°C for 2-3 minutes, and dried to obtain MAH-GMA co-grafted modified PP resin.

[0023] As a further embodiment of the present invention: the mass ratio of polypropylene resin, maleic anhydride, glycidyl methacrylate, styrene, and dicumyl peroxide is 100g: 2-4g: 1.5-3g: 0.35-0.75g: 0.2-0.5g.

[0024] As a further aspect of the present invention, the preparation method of epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid includes the following steps:

[0025] Under a nitrogen atmosphere, lithium bis(trifluoromethanesulfonyl)imide, reaction solvent, and catalyst were added to a reaction flask and dispersed. The temperature was controlled at 55-60℃, and epichlorohydrin was added for dispersion. The temperature was controlled at 60-70℃ and the reaction was maintained for 3-6 hours. The mixture was then cooled, filtered, evaporated under reduced pressure, and dried to obtain epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid.

[0026] As a further aspect of the present invention: the reaction solvent is composed of anhydrous acetonitrile and anhydrous ethanol in a volume ratio of 4:1; the catalyst is composed of anhydrous potassium carbonate and tetrabutylammonium bromide in a mass ratio of 8-15:1-2; and the addition ratio of lithium bis(trifluoromethanesulfonylimide), reaction solvent, catalyst, and epichlorohydrin is 100g:500-800mL:9-17g:25-40g.

[0027] The preparation method of high-toughness conductive polypropylene sheet for power batteries according to any of the above-mentioned methods includes the following steps: according to the raw material ratio, polypropylene resin, MAH-GMA co-grafted modified PP resin, composite conductive filler, crosslinking penetration promoter, toughening modifier, compatibilizer, antioxidant, and lubricant are mixed and then added to a twin-screw extruder for melt mixing, extrusion, cooling, and granulation to obtain masterbatch; the masterbatch is dried, extruded and plasticized, calendered / cast, trimmed, and wound to obtain high-toughness conductive polypropylene sheet.

[0028] The beneficial effects of this invention are:

[0029] (1) Improve the electrical conductivity of the material

[0030] This application utilizes a composite of conductive carbon black and carbon nanotubes as conductive fillers, modified with aminosilane coupling agents and ionic liquids, and finally encapsulated with dopamine and tetraethyl orthosilicate to obtain a composite conductive filler. The zero-dimensional conductive carbon black fills the void nodes of the one-dimensional carbon nanotube interwoven network, forming a dense three-dimensional "grape bunch" conductive percolation network, with the number of conductive pathways increasing exponentially compared to a single filler system. This application utilizes KH550 to introduce reactive -NH2 onto the filler surface; epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid is grafted onto it through a ring-opening reaction to form covalent bonds. The large volume of anions in the epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid generates a steric hindrance effect, which, combined with the hydrophilicity of the PDA layer and the isolating effect of nano-SiO2, synergistically prevents secondary agglomeration of the filler. The lithium bis(trifluoromethanesulfonyl)imide grafted onto the filler surface constructs local ion transport channels in the matrix, synergistically with the electronic conductivity of the conductive carbon black and carbon nanotubes, further reducing the overall resistivity.

[0031] (2) Improve mechanical properties

[0032] This application uses MAH-GMA co-grafted modified PP resin to replace part of the polypropylene resin. Maleic anhydride and glycidyl methacrylate grafted onto the PP backbone provide bifunctional groups of anhydride and epoxy groups. The anhydride groups can undergo imidization reactions with the amino groups of the PDA layer on the surface of the composite conductive filler, and the epoxy groups can undergo ring-opening addition reactions with the amino groups, forming a double chemical bond. This molecular bridge structure upgrades the interfacial bonding between the composite conductive filler and the matrix from physical entanglement to chemical bonding, significantly improving stress transfer efficiency and macroscopically exhibiting a significant increase in tensile strength.

[0033] This application incorporates DCP / TAIC as a crosslinking and penetration enhancer in the composition, synergistically and moderately reinforcing the matrix through crosslinking. The thermal decomposition of DCP generates free radicals, initiating coupling between polypropylene resin molecular chains. The three allyl groups of TAIC participate in bridging crosslinking, forming a uniform three-dimensional network. This network enhances matrix strength without excessively restricting molecular chain movement, achieving a synergistic effect of reinforcement and toughening.

[0034] This application adds POE-g-MAH or SEBS-g-MAH as toughening modifiers to the composition. The elastomer backbone of the toughening modifier is dispersed in the polypropylene matrix, acting as stress concentration points to induce crazes and shear bands, significantly consuming impact energy and improving elongation at break and impact toughness. Simultaneously, the grafted maleic anhydride groups undergo imidization reactions with the amino groups (derived from KH550 amination and PDA coating) on ​​the surface of the composite conductive filler, forming chemical bonds. This chemical anchoring firmly binds the elastomer to the filler / matrix interface, forming an elastomer-filler core-shell structure—an elastomer shell layer acting as a stress buffer layer, avoiding stress concentration at the filler / matrix interface, synergistically improving tensile strength and impact toughness, and preventing phase separation of the elastomer and filler in traditional physical blending. This application utilizes the toughening modifier and crosslinking penetration enhancer to construct a semi-interpenetrating network structure, achieving a balance between rigidity and toughness.

[0035] (3) Balancing bending durability and electrical conductivity

[0036] In this application, the composite conductive filler, compatibilizer, and toughening modifier are tightly bonded to the matrix through multiple chemical bonding mechanisms. Bending stress is uniformly transferred to the matrix through chemical bonds, preventing concentration at the interface and thus avoiding debonding. This application adds DCP / TAIC as a crosslinking and penetration-enhancing agent to the composition. The three-dimensional crosslinking network constructed by DCP / TAIC locks the conductive filler within the matrix's mesh. During bending, the plastic flow of the matrix is ​​restricted by the crosslinking network, significantly reducing the relative displacement of the conductive filler and maintaining the integrity of the conductive pathway. The SiO2 shell of the composite conductive filler is a rigid nanoshell formed by in-situ growth of TEOS, which reinforces and protects the conductive filler, preventing bending stress from directly acting on it and causing cracking or breakage.

[0037] (4) Significantly improved resistance to damp heat aging

[0038] This application utilizes epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid to treat aminated modified carbon fillers. The CF and SN bonds are highly stable, with a thermal decomposition temperature >300℃, and it is hydrophobic, preventing hydrolysis and the generation of corrosive substances under humid and hot conditions. This application also utilizes TEOS and PDA coating to treat the epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid-modified aminated modified carbon fillers. Furthermore, this application utilizes dopamine hydrochloride to coat the surface of the epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid-modified aminated modified carbon fillers with a PDA layer. The PDA layer contains abundant catechol groups, possessing free radical scavenging capabilities, and forms a synergistic antioxidant system with the antioxidant (Irganox 1010 / 168) in the formulation, slowing down the thermo-oxidative degradation process of the PP matrix under humid and hot conditions. This application utilizes a uniform and dense nano-SiO2 shell generated in situ by TEOS. This shell forms an effective physical barrier, blocking the penetration of water molecules and oxygen, and protecting the interface between the conductive filler and the matrix from chemical degradation caused by humid heat erosion.

[0039] (5) Excellent resistance to electrolyte corrosion, suitable for power battery operating conditions

[0040] This application incorporates a composite conductive filler into conductive polypropylene sheets. The outermost layer of the composite conductive filler, TEOS-grown in-situ SiO2, together with the intermediate PDA layer, forms a bifunctional shielding layer. This layer exhibits excellent chemical inertness and low permeability to polar organic solvent molecules (EC, DMC, EMC) and LiPF6 in the electrolyte, effectively blocking the capillary penetration of small electrolyte molecules along the filler / matrix interface. Lithium bis(trifluoromethanesulfonyl)imide is grafted onto the filler surface via ring-opening covalent bonds between epoxy and amino groups, preventing dissolution and desorption by the electrolyte and maintaining the integrity of the interface structure. The grafted lithium bis(trifluoromethanesulfonyl)imide forms a chemically bonded hydrophobic barrier on the filler surface, further repelling the penetration of polar electrolytes.

[0041] This application further incorporates POE-g-MAH or SEBS-g-MAH as a toughening modifier and DCP / TAIC as a crosslinking and penetration-promoting agent into the conductive polypropylene sheet. The MAH groups of the toughening modifier chemically bond with the amino groups on the filler surface, firmly anchoring the elastomer at the filler / matrix interface. This acts as a sacrificial buffer layer, preferentially absorbing and blocking electrolyte erosion, thus delaying the interface failure process. The three-dimensional crosslinked network constructed by DCP / TAIC improves the density of the matrix, reduces the diffusion coefficient of small electrolyte molecules in the matrix, and slows down the erosion of the internal interface.

[0042] This invention uses polypropylene as the matrix, introduces MAH-GMA double-grafted modified PP to construct a reactive interface system, and adds composite conductive filler to solve the problems of mutual restriction between conductivity and toughness of traditional conductive polypropylene sheets, easy agglomeration of filler, failure of conductive interface due to electrolyte / humid heat environment, and insufficient sensitivity of micro-leakage detection. It is suitable for power battery leakage detection with tensile coating, long-term vibration, and humid heat service conditions. Detailed Implementation

[0043] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0044] Example 1: The preparation method of MAH-GMA co-grafted modified PP resin includes the following steps: 100g of polypropylene resin (purchased from Dushanzi Petrochemical Company, grade T30S polypropylene resin, melt flow rate of 3.2g / 10min), 2g of maleic anhydride, 1.5g of glycidyl methacrylate, 0.35g of styrene, and 0.2g of dicumyl peroxide are blended and fed into a twin-screw extruder. The mixture is extruded and granulated at 175℃ for 2min, and then dried to obtain MAH-GMA co-grafted modified PP resin.

[0045] The preparation method of composite conductive filler includes the following steps:

[0046] A1: 8g of conductive carbon black (E900 grade conductive carbon black purchased from Sichuan Zheng Hao Special Carbon Black Technology Co., Ltd.), 2g of carbon nanotubes (multi-walled carbon nanotubes purchased from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences), 72mL of anhydrous ethanol, and 8mL of deionized water were added to a reaction flask for dispersion. Glacial acetic acid was added to adjust the pH to 4, and 4g of KH550 was added for dispersion. The temperature was controlled at 60℃ and the reaction was kept at this temperature for 2h. The mixture was then filtered, washed, and dried to obtain the aminated modified carbon filler.

[0047] A2: Under a nitrogen atmosphere, 100g of lithium bis(trifluoromethanesulfonyl)imide, 400mL of anhydrous acetonitrile, 100mL of anhydrous ethanol, 8g of anhydrous potassium carbonate, and 1g of tetrabutylammonium bromide were added to a reaction flask and dispersed. The temperature was controlled at 55℃, and 25g of epichlorohydrin was added for dispersion. The temperature was controlled at 60℃ and the reaction was maintained for 3h. After cooling, the mixture was filtered, evaporated under reduced pressure, and dried to obtain an epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid.

[0048] 10g of aminated modified carbon filler and 80mL of anhydrous ethanol were added to a reaction flask for dispersion. 0.2g of triethylamine was added for dispersion, and 0.4g of epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid was added. The temperature was controlled at 70℃ and the reaction was kept at this temperature for 1h. After centrifugation, washing and drying, the intermediate was obtained.

[0049] A3: 10g of intermediate, 150mL of Tris-HCl buffer (pH=8.5, 10mM), and 40mL of anhydrous ethanol were added to a reaction flask for dispersion. 0.5g of dopamine hydrochloride was added, and the mixture was stirred at room temperature for 2h. 0.5mL of tetraethyl orthosilicate was added for dispersion. 25wt% ammonia was added to adjust the pH to 8. The temperature was controlled at 40℃ and the reaction was kept at this temperature for 6h. After centrifugation, washing, and drying, the composite conductive filler was obtained.

[0050] A method for preparing a high-toughness conductive polypropylene sheet for power batteries includes the following steps: 70 parts by weight of polypropylene resin (purchased from Dushanzi Petrochemical Company, grade T30S, melt flow rate 3.2 g / 10 min), 15 parts by weight of MAH-GMA co-grafted modified PP resin prepared in Example 1, 15 parts by weight of composite conductive filler prepared in Example 1, 0.5 parts by weight of dicumyl peroxide, 1.5 parts by weight of triallyl isocyanurate, 8 parts by weight of POE-g-MAH toughening agent (purchased from Foshan Nanhai Baichen Polymer New Materials Co., Ltd., grade PC33), and 3.5 parts by weight of PP-g-MAH compatibilizer (purchased from Nanjing Julong Chemical Co., Ltd., grafting rate 0.7%, melt flow rate 3.2 g / 10 min). The mixture of 0.3 parts by weight of antioxidant 1010, 0.3 parts by weight of antioxidant 168, and 1 part by weight of calcium stearate is fed into a twin-screw extruder (the twin-screw extruder temperature is set as follows: Zone 1 170℃, Zone 2 180℃, Zone 3 190℃, and Die / die head 185℃). The molten extrudate is cooled and shaped in a water bath and cut into granules by an automatic cutter to obtain granules. The granules are then dried in a dryer at 85℃ for 4 hours and fed into the twin-screw extruder. After melting, the material flows out from the T-die and enters a four-roll calender (roll temperature 60℃). The melt passes through the gaps between the rolls in sequence and is shaped under pressure and cooling. The traction device pulls the sheet at a constant speed to obtain a high-toughness conductive polypropylene sheet with a sheet thickness of 1mm.

[0051] Example 2: The preparation method of MAH-GMA co-grafted modified PP resin includes the following steps: 100g of polypropylene resin (purchased from Dushanzi Petrochemical Company, grade T30S polypropylene resin, melt flow rate of 3.2g / 10min), 3g of maleic anhydride, 2.2g of glycidyl methacrylate, 0.55g of styrene, and 0.35g of dicumyl peroxide are blended and fed into a twin-screw extruder. The mixture is extruded and granulated at 180℃ for 3min, and then dried to obtain MAH-GMA co-grafted modified PP resin.

[0052] The preparation method of composite conductive filler includes the following steps:

[0053] A1: 8g of conductive carbon black (E900 grade conductive carbon black purchased from Sichuan Zheng Hao Special Carbon Black Technology Co., Ltd.), 2g of carbon nanotubes (multi-walled carbon nanotubes purchased from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences), 90mL of anhydrous ethanol, and 10mL of deionized water were added to a reaction flask for dispersion. Glacial acetic acid was added to adjust the pH to 5, and 6g of KH550 was added for dispersion. The temperature was controlled at 65℃ and the reaction was kept at this temperature for 3h. The mixture was then filtered, washed, and dried to obtain aminated modified carbon filler.

[0054] A2: Under a nitrogen atmosphere, 100g of lithium bis(trifluoromethanesulfonyl)imide, 480mL of anhydrous acetonitrile, 120mL of anhydrous ethanol, 12g of anhydrous potassium carbonate, and 1.5g of tetrabutylammonium bromide were added to a reaction flask and dispersed. The temperature was controlled at 60℃. Then, 32.5g of epichlorohydrin was added and dispersed. The temperature was controlled at 65℃ and the reaction was maintained for 4.5h. After cooling, the mixture was filtered, evaporated under reduced pressure, and dried to obtain an epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid.

[0055] 10g of aminated modified carbon filler and 100mL of anhydrous ethanol were added to a reaction flask for dispersion. 0.35g of triethylamine was added for dispersion, and 0.7g of epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid was added. The temperature was controlled at 75℃ and the reaction was kept at this temperature for 1.5h. After centrifugation, washing, and drying, the intermediate was obtained.

[0056] A3: 10g of intermediate, 200mL of Tris-HCl buffer (pH=8.5, 10mM), and 60mL of anhydrous ethanol were added to a reaction flask for dispersion. 1g of dopamine hydrochloride was added, and the mixture was stirred at room temperature for 2.5h. 1.2mL of tetraethyl orthosilicate was added for dispersion, and 25wt% ammonia was added to adjust the pH to 8. The temperature was controlled at 50℃ and the reaction was kept at this temperature for 9h. After centrifugation, washing, and drying, the composite conductive filler was obtained.

[0057] A method for preparing high-toughness conductive polypropylene sheets for power batteries, compared with Example 1, only the MAH-GMA co-grafted modified PP resin and composite conductive filler prepared in Example 1 are replaced in equal amounts with MAH-GMA co-grafted modified PP resin and composite conductive filler prepared in Example 2. The remaining components and preparation methods are completely consistent with Example 1.

[0058] Example 3: The preparation method of MAH-GMA co-grafted modified PP resin includes the following steps: 100g of polypropylene resin (purchased from Dushanzi Petrochemical Company, grade T30S polypropylene resin, melt flow rate of 3.2g / 10min), 4g of maleic anhydride, 3g of glycidyl methacrylate, 0.75g of styrene, and 0.5g of dicumyl peroxide are blended and fed into a twin-screw extruder. The mixture is extruded and granulated at 190℃ for 3min, and then dried to obtain MAH-GMA co-grafted modified PP resin.

[0059] The preparation method of composite conductive filler includes the following steps:

[0060] A1: 8g of conductive carbon black (E900 grade conductive carbon black purchased from Sichuan Zheng Hao Special Carbon Black Technology Co., Ltd.), 2g of carbon nanotubes (multi-walled carbon nanotubes purchased from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences), 108mL of anhydrous ethanol, and 12mL of deionized water were added to a reaction flask for dispersion. Glacial acetic acid was added to adjust the pH to 5, and 8g of KH550 was added for dispersion. The temperature was controlled at 70℃ and the reaction was kept at this temperature for 4h. The mixture was then filtered, washed, and dried to obtain aminated modified carbon filler.

[0061] A2: Under a nitrogen atmosphere, 100g of lithium bis(trifluoromethanesulfonyl)imide, 640mL of anhydrous acetonitrile, 160mL of anhydrous ethanol, 15g of anhydrous potassium carbonate, and 2g of tetrabutylammonium bromide were added to a reaction flask and dispersed. The temperature was controlled at 60℃, and 40g of epichlorohydrin was added for dispersion. The temperature was controlled at 70℃ and the reaction was maintained for 6h. After cooling, the mixture was filtered, evaporated under reduced pressure, and dried to obtain an epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid.

[0062] 10g of aminated modified carbon filler and 120mL of anhydrous ethanol were added to a reaction flask for dispersion. 0.5g of triethylamine was added for dispersion, and 1g of epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid was added. The temperature was controlled at 80℃ and the reaction was kept at this temperature for 2h. After centrifugation, washing and drying, the intermediate was obtained.

[0063] A3: 10g of intermediate, 250mL of Tris-HCl buffer (pH=8.5, 10mM), and 80mL of anhydrous ethanol were added to a reaction flask for dispersion. 1.5g of dopamine hydrochloride was added, and the mixture was stirred at room temperature for 4h. 2mL of tetraethyl orthosilicate was added for dispersion, and 25wt% ammonia was added to adjust the pH to 9. The temperature was controlled at 60℃ and the reaction was kept at this temperature for 12h. The mixture was then centrifuged, washed, and dried to obtain the composite conductive filler.

[0064] A method for preparing high-toughness conductive polypropylene sheets for power batteries, compared with Example 1, only the MAH-GMA co-grafted modified PP resin and composite conductive filler prepared in Example 1 are replaced in equal amounts with MAH-GMA co-grafted modified PP resin and composite conductive filler prepared in Example 3. The remaining components and preparation methods are completely consistent with Example 1.

[0065] Comparative Example 1: A method for preparing a high-toughness conductive polypropylene sheet for power batteries. Compared with Example 1, only the MAH-GMA co-grafted modified PP resin prepared in Example 1 was replaced in equal amounts with polypropylene resin (polypropylene resin of grade T30S purchased from Dushanzi Petrochemical Company, with a melt flow rate of 3.2 g / 10 min). The remaining components and preparation methods were completely consistent with Example 1.

[0066] Comparative Example 2: The preparation method of the composite conductive filler includes the following steps: 8g of conductive carbon black (conductive carbon black of grade E900 purchased from Sichuan Zheng Hao Special Carbon Black Technology Co., Ltd.) and 2g of carbon nanotubes (multi-walled carbon nanotubes purchased from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences) are blended to obtain the composite conductive filler.

[0067] A method for preparing a high-toughness conductive polypropylene sheet for power batteries, compared with Example 1, only the composite conductive filler prepared in Example 1 is replaced in equal amounts with the composite conductive filler prepared in Comparative Example 2, and the remaining components and preparation methods are completely consistent with Example 1.

[0068] Comparative Example 3: The preparation method of the composite conductive filler includes the following steps:

[0069] A1: 8g of conductive carbon black (E900 grade conductive carbon black purchased from Sichuan Zheng Hao Special Carbon Black Technology Co., Ltd.), 2g of carbon nanotubes (multi-walled carbon nanotubes purchased from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences), 90mL of anhydrous ethanol, and 10mL of deionized water were added to a reaction flask for dispersion. Glacial acetic acid was added to adjust the pH to 5, and 6g of KH550 was added for dispersion. The temperature was controlled at 65℃ and the reaction was kept at this temperature for 3h. The mixture was then filtered, washed, and dried to obtain aminated modified carbon filler.

[0070] A2: 10g of aminated modified carbon filler, 200mL of Tris-HCl buffer (pH=8.5, 10mM), and 60mL of anhydrous ethanol were added to a reaction flask for dispersion. 1g of dopamine hydrochloride was added, and the mixture was stirred at room temperature for 2.5h. 1.2mL of tetraethyl orthosilicate was added for dispersion, and 25wt% ammonia was added to adjust the pH to 8. The temperature was controlled at 50℃ and the reaction was kept at this temperature for 9h. After centrifugation, washing, and drying, the composite conductive filler was obtained.

[0071] A method for preparing a high-toughness conductive polypropylene sheet for power batteries, compared with Example 1, only the composite conductive filler prepared in Example 1 is replaced in equal amounts with the composite conductive filler prepared in Comparative Example 3, and the remaining components and preparation methods are completely consistent with Example 1.

[0072] Comparative Example 4: The preparation method of the composite conductive filler includes the following steps:

[0073] A1: 8g of conductive carbon black (E900 grade conductive carbon black purchased from Sichuan Zheng Hao Special Carbon Black Technology Co., Ltd.), 2g of carbon nanotubes (multi-walled carbon nanotubes purchased from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences), 90mL of anhydrous ethanol, and 10mL of deionized water were added to a reaction flask for dispersion. Glacial acetic acid was added to adjust the pH to 5, and 6g of KH550 was added for dispersion. The temperature was controlled at 65℃ and the reaction was kept at this temperature for 3h. The mixture was then filtered, washed, and dried to obtain aminated modified carbon filler.

[0074] A2: 10g of aminated modified carbon filler and 100mL of anhydrous ethanol were added to a reaction flask for dispersion, 0.35g of triethylamine was added for dispersion, and 0.7g of lithium bis(trifluoromethanesulfonyl)imide was added. The temperature was controlled at 75℃ and the reaction was kept at this temperature for 1.5h. After centrifugation, washing and drying, the intermediate was obtained.

[0075] A3: 10g of intermediate, 200mL of Tris-HCl buffer (pH=8.5, 10mM), and 60mL of anhydrous ethanol were added to a reaction flask for dispersion. 1g of dopamine hydrochloride was added, and the mixture was stirred at room temperature for 2.5h. 1.2mL of tetraethyl orthosilicate was added for dispersion. 25wt% ammonia was added to adjust the pH to 8. The temperature was controlled at 50℃ and the reaction was kept at this temperature for 9h. After centrifugation, washing, and drying, the composite conductive filler was obtained.

[0076] A method for preparing a high-toughness conductive polypropylene sheet for power batteries, compared with Example 1, is that the composite conductive filler prepared in Example 1 is replaced in equal amounts with the composite conductive filler prepared in Comparative Example 4, and the remaining components and preparation methods are completely consistent with Example 1.

[0077] Comparative Example 5: The preparation method of the composite conductive filler includes the following steps:

[0078] A1: 8g of conductive carbon black (E900 grade conductive carbon black purchased from Sichuan Zheng Hao Special Carbon Black Technology Co., Ltd.), 2g of carbon nanotubes (multi-walled carbon nanotubes purchased from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences), 90mL of anhydrous ethanol, and 10mL of deionized water were added to a reaction flask for dispersion. Glacial acetic acid was added to adjust the pH to 5, and 6g of KH550 was added for dispersion. The temperature was controlled at 65℃ and the reaction was kept at this temperature for 3h. The mixture was then filtered, washed, and dried to obtain aminated modified carbon filler.

[0079] A2: Under a nitrogen atmosphere, 100g of lithium bis(trifluoromethanesulfonyl)imide, 480mL of anhydrous acetonitrile, 120mL of anhydrous ethanol, 12g of anhydrous potassium carbonate, and 1.5g of tetrabutylammonium bromide were added to a reaction flask and dispersed. The temperature was controlled at 60℃. Then, 32.5g of epichlorohydrin was added and dispersed. The temperature was controlled at 65℃ and the reaction was maintained for 4.5h. After cooling, the mixture was filtered, evaporated under reduced pressure, and dried to obtain an epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid.

[0080] 10g of aminated modified carbon filler and 100mL of anhydrous ethanol were added to a reaction flask for dispersion. 0.35g of triethylamine was added for dispersion, and 0.7g of epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid was added. The temperature was controlled at 75℃ and the reaction was maintained for 1.5h. After centrifugation, washing and drying, the composite conductive filler was obtained.

[0081] A method for preparing a high-toughness conductive polypropylene sheet for power batteries, compared with Example 1, only the composite conductive filler prepared in Example 1 is replaced in equal amounts with the composite conductive filler prepared in Comparative Example 5, and the remaining components and preparation methods are completely consistent with Example 1.

[0082] Comparative Example 6: The preparation method of the composite conductive filler includes the following steps:

[0083] A1: 10g of conductive carbon black (conductive carbon black of brand E900 purchased from Sichuan Zheng Hao Special Carbon Black Technology Co., Ltd.), 90mL of anhydrous ethanol and 10mL of deionized water were added to the reaction flask for dispersion. Glacial acetic acid was added to adjust the pH to 5. 6g of KH550 was added for dispersion. The temperature was controlled at 65℃ and the reaction was kept at this temperature for 3h. The mixture was then filtered, washed and dried to obtain the aminated modified carbon filler.

[0084] A2: Under a nitrogen atmosphere, 100g of lithium bis(trifluoromethanesulfonyl)imide, 480mL of anhydrous acetonitrile, 120mL of anhydrous ethanol, 12g of anhydrous potassium carbonate, and 1.5g of tetrabutylammonium bromide were added to a reaction flask and dispersed. The temperature was controlled at 60℃. Then, 32.5g of epichlorohydrin was added and dispersed. The temperature was controlled at 65℃ and the reaction was maintained for 4.5h. After cooling, the mixture was filtered, evaporated under reduced pressure, and dried to obtain an epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid.

[0085] 10g of aminated modified carbon filler and 100mL of anhydrous ethanol were added to a reaction flask for dispersion. 0.35g of triethylamine was added for dispersion, and 0.7g of epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid was added. The temperature was controlled at 75℃ and the reaction was kept at this temperature for 1.5h. After centrifugation, washing, and drying, the intermediate was obtained.

[0086] A3: 10g of intermediate, 200mL of Tris-HCl buffer (pH=8.5, 10mM), and 60mL of anhydrous ethanol were added to a reaction flask for dispersion. 1g of dopamine hydrochloride was added, and the mixture was stirred at room temperature for 2.5h. 1.2mL of tetraethyl orthosilicate was added for dispersion. 25wt% ammonia was added to adjust the pH to 8. The temperature was controlled at 50℃ and the reaction was kept at this temperature for 9h. After centrifugation, washing, and drying, the composite conductive filler was obtained.

[0087] A method for preparing a high-toughness conductive polypropylene sheet for power batteries, compared with Example 1, only replaces the composite conductive filler prepared in Example 1 with the composite conductive filler prepared in Comparative Example 6 in equal amounts, while the remaining components and preparation methods are completely consistent with Example 1.

[0088] Comparative Example 7: The preparation method of the composite conductive filler includes the following steps:

[0089] A1: 10g of carbon nanotubes (multi-walled carbon nanotubes purchased from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences), 90mL of anhydrous ethanol and 10mL of deionized water were added to the reaction flask for dispersion. Glacial acetic acid was added to adjust the pH to 5. 6g of KH550 was added for dispersion. The temperature was controlled at 65℃ and the reaction was kept at this temperature for 3h. The mixture was then filtered, washed and dried to obtain the aminated modified carbon filler.

[0090] A2: Under a nitrogen atmosphere, 100g of lithium bis(trifluoromethanesulfonyl)imide, 480mL of anhydrous acetonitrile, 120mL of anhydrous ethanol, 12g of anhydrous potassium carbonate, and 1.5g of tetrabutylammonium bromide were added to a reaction flask and dispersed. The temperature was controlled at 60℃. Then, 32.5g of epichlorohydrin was added and dispersed. The temperature was controlled at 65℃ and the reaction was maintained for 4.5h. After cooling, the mixture was filtered, evaporated under reduced pressure, and dried to obtain an epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid.

[0091] 10g of aminated modified carbon filler and 100mL of anhydrous ethanol were added to a reaction flask for dispersion. 0.35g of triethylamine was added for dispersion, and 0.7g of epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid was added. The temperature was controlled at 75℃ and the reaction was kept at this temperature for 1.5h. After centrifugation, washing, and drying, the intermediate was obtained.

[0092] A3: 10g of intermediate, 200mL of Tris-HCl buffer (pH=8.5, 10mM), and 60mL of anhydrous ethanol were added to a reaction flask for dispersion. 1g of dopamine hydrochloride was added, and the mixture was stirred at room temperature for 2.5h. 1.2mL of tetraethyl orthosilicate was added for dispersion. 25wt% ammonia was added to adjust the pH to 8. The temperature was controlled at 50℃ and the reaction was kept at this temperature for 9h. After centrifugation, washing, and drying, the composite conductive filler was obtained.

[0093] A method for preparing a high-toughness conductive polypropylene sheet for power batteries, compared with Example 1, only the composite conductive filler prepared in Example 1 is replaced in equal amounts with the composite conductive filler prepared in Comparative Example 7, and the remaining components and preparation methods are completely consistent with Example 1.

[0094] Comparative Example 8: A method for preparing a high-toughness conductive polypropylene sheet for power batteries. Compared with Example 1, only 1.5 parts by weight of triallyl isocyanurate was removed from Example 1. The remaining components and preparation method are completely the same as in Example 1.

[0095] Performance testing

[0096] (1) Mechanical properties

[0097] Tensile strength and elongation at break: According to GB / T 1040-2022 "Determination of tensile properties of plastics - Part 2: Test conditions for molded and extruded plastics", dumbbell type I specimen, thickness 1 mm, tensile rate 20 mm / min, the test results are shown in Table 1.

[0098] Notched impact strength of cantilever beam: According to GB / T 1843-2008 "Determination of impact strength of plastic cantilever beam", notched specimen, thickness 1mm, the test results are shown in Table 1;

[0099] Table 1: Statistical Table of Mechanical Property Test Data for Examples 1-3 and Comparative Examples 1-8

[0100] Example 1 27.8 128 9.2 Example 2 31.2 162 11.8 Example 3 29.5 135 10.1 Comparative Example 1 22.3 95 6.5 Comparative Example 2 20.8 72 5.8 Comparative Example 3 24.1 105 7.2 Comparative Example 4 23.5 98 6.8 Comparative Example 5 26.2 118 8.5 Comparative Example 6 22.5 88 6.2 Comparative Example 7 19.6 65 4.8 Comparative Example 8 18.6 142 8.6

[0101] As shown in Table 1, the polypropylene sheet prepared in this application has excellent mechanical properties.

[0102] (2) Electrical conductivity

[0103] Volume resistivity: GB / T 15662-1995 "Test Method for Volume Resistivity of Conductive and Antistatic Plastics", using 1mm thick molded sheets cut into 80mm×80mm square materials for power supply performance testing. Room temperature resistance greater than 10. 3 When the resistance is below Ω, a ZC46A high-resistivity meter manufactured by Shanghai Precision Scientific Instruments Co., Ltd., equipped with ZC36 electrodes, is used for testing. 3 The Ω value was measured using an SDY24 four-probe tester from the Guangzhou Semiconductor Materials Research Institute; the test results are shown in Table 1.

[0104] Repeated bending durability test: The samples prepared in Examples 1-3 and Comparative Examples 1-8 were bent at an angle of 180°, a bending rate of 30 times / min, and 120 times. The resistivity after bending was measured and the resistance change rate was calculated. The test results are shown in Table 2.

[0105] Moist heat aging resistance: According to GB / T 12000-2017 "Determination of the effects of exposure of plastics to damp heat, water spray and salt spray", aging was carried out at 85℃ and 85% relative humidity for 1000h; resistivity was tested after aging and the resistivity change rate was calculated; the test results are shown in Table 2.

[0106] Electrolyte immersion resistance: Plastics were immersed in electrolyte (EC / DMC+LiPF6) at 60℃ for 300 hours according to ISO 175:2010 "Plastics - Resistance to immersion in liquid chemicals". After cleaning and drying, the resistivity was measured and the resistivity change rate was calculated. The test results are shown in Table 2.

[0107] Table 2: Statistical table of conductivity test data for Examples 1-3 and Comparative Examples 1-8

[0108] Example 1 <![CDATA[8.2×10 4 ]]> 11.2 15.6 18.5 Example 2 <![CDATA[5.6×10 4 ]]> 7.8 8.2 10.6 Example 3 <![CDATA[7.5×10 4 ]]> 9.5 12.4 14.2 Comparative Example 1 <![CDATA[2.3×10 5 ]]> 25.6 28.7 35.8 Comparative Example 2 <![CDATA[8.7×10 6 ]]> 48.3 45.2 68.5 Comparative Example 3 <![CDATA[5.4×10 5 ]]> 18.7 32.5 28.5 Comparative Example 4 <![CDATA[2.8×10 5 ]]> 22.4 30.8 32.6 Comparative Example 5 <![CDATA[6.8×10 4 ]]> 13.6 56.4 22.4 Comparative Example 6 <![CDATA[2.1×10 6 ]]> 36.8 38.5 42.5 Comparative Example 7 <![CDATA[4.5×10 5 ]]> 15.2 26.8 25.6 Comparative Example 8 <![CDATA[2.5×10 5 ]]> 26.4 35.2 38.5

[0109] As shown in Table 2, the polypropylene sheet prepared in this application is conductive and maintains good conductivity even after bending, damp heat aging, and contact with electrolyte.

[0110] (3) Durability

[0111] Moist heat aging resistance: According to GB / T 12000-2017 "Determination of the effects of exposure to damp heat, water spray and salt spray on plastics", the aging was carried out at 85℃ and 85% relative humidity for 1000h; after aging, the tensile strength and cantilever beam notched impact strength were tested, and the tensile strength retention rate and impact strength retention rate were calculated; the test results are shown in Table 3.

[0112] Electrolyte immersion resistance: Plastics were immersed in electrolyte (EC / DMC+LiPF6) at 60℃ for 300h according to ISO 175:2010 "Immersion in liquid chemicals on plastics". After cleaning and drying, tensile strength and elongation at break were tested, and tensile strength retention rate and elongation at break change rate were calculated. The test results are shown in Table 3.

[0113] Table 3: Statistical Table of Durability Performance Test Data for Examples 1-3 and Comparative Examples 1-8

[0114] Example 1 15.6 84.2 81.6 -10.2 Example 2 8.2 93.1 89.7 -4.8 Example 3 12.4 88.5 85.3 -6.5 Comparative Example 1 28.7 72.6 70.2 -22.5 Comparative Example 2 45.2 65.4 48.6 -45.8 Comparative Example 3 32.5 76.8 72.5 -18.6 Comparative Example 4 30.8 74.2 68.8 -20.4 Comparative Example 5 56.4 62.8 78.5 -12.5 Comparative Example 6 38.5 70.5 66.3 -28.6 Comparative Example 7 26.8 68.2 62.8 -35.2 Comparative Example 8 35.2 68.5 65.2 -20.8

[0115] As shown in Table 3, the polypropylene sheet prepared in this application maintains good mechanical properties even after wet heat aging and contact with electrolyte.

[0116] The foregoing has provided a detailed description of one embodiment of the present invention, but this description is merely a preferred embodiment and should not be construed as limiting the scope of the invention. All equivalent variations and modifications made within the scope of the claims of this invention should still fall within the patent coverage of this invention.

Claims

1. A high-toughness conductive polypropylene sheet for power batteries, characterized in that, The polypropylene sheet comprises the following raw materials in parts by weight: 60-75 parts by weight of polypropylene resin, 10-20 parts by weight of MAH-GMA co-grafted modified PP resin, 10-22 parts by weight of composite conductive filler, 1-2.8 parts by weight of crosslinking penetration enhancer, 5-12 parts by weight of toughening modifier, 2-5 parts by weight of compatibilizer, 0.3-1 parts by weight of antioxidant, and 0.5-1.5 parts by weight of lubricant; The preparation method of the composite conductive filler includes the following steps: A1: Add conductive carbon filler and ethanol solution to a reaction flask for dispersion, add glacial acetic acid to adjust pH to 4-5, add KH550 for dispersion, control the temperature at 60-70℃ and keep the reaction at this temperature for 2-4 hours, filter, wash and dry to obtain aminated modified carbon filler. A2: Aminated modified carbon filler and anhydrous ethanol were added to a reaction flask for dispersion, triethylamine was added for dispersion, epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid was added, the temperature was controlled at 70-80℃ and the reaction was kept at this temperature for 1-2 hours, centrifuged, washed and dried to obtain the intermediate; A3: Add the intermediate, Tris-HCl buffer, and anhydrous ethanol to the reaction flask for dispersion, add dopamine hydrochloride, and stir the reaction at room temperature for 2-4 hours; add tetraethyl orthosilicate for dispersion, adjust the pH to 8-9, control the temperature at 40-60℃, and keep the reaction at this temperature for 6-12 hours. Centrifuge, wash, and dry to obtain the composite conductive filler.

2. The high-toughness conductive polypropylene sheet for power batteries according to claim 1, characterized in that, The crosslinking penetration enhancer is composed of dicumyl peroxide and triallyl isocyanurate in a mass ratio of 0.2-0.8:0.8-2; The toughening modifier is POE-g-MAH or SEBS-g-MAH; The compatibilizer is a PP-g-MAH compatibilizer; The antioxidant is composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 1-2:1; The lubricant is calcium stearate.

3. The high-toughness conductive polypropylene sheet for power batteries according to claim 1, characterized in that, In A1, the ethanol solution is composed of anhydrous ethanol and deionized water in a volume ratio of 9:1; the conductive carbon filler is composed of conductive carbon black and carbon nanotubes in a mass ratio of 3-5:1; the addition ratio of KH550, ethanol solution and conductive carbon filler is 4-8g: 80-120mL: 10g.

4. The high-toughness conductive polypropylene sheet for power batteries according to claim 1, characterized in that, The addition ratio of aminated modified carbon filler, anhydrous ethanol, triethylamine, and epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid in A2 is 10g: 80-120mL: 0.2-0.5g: 0.4-1g.

5. A high-toughness conductive polypropylene sheet for power batteries according to claim 1, characterized in that, The addition amounts of intermediate, Tris-HCl buffer, anhydrous ethanol, dopamine hydrochloride, and tetraethyl orthosilicate in A3 are 10g: 150-250mL: 40-80mL: 0.5-1.5g: 0.5-2mL.

6. A high-toughness conductive polypropylene sheet for power batteries according to claim 1, characterized in that, The preparation method of the MAH-GMA co-grafted modified PP resin includes the following steps: polypropylene resin, maleic anhydride, glycidyl methacrylate, styrene, and dicumyl peroxide are blended and fed into a twin-screw extruder, extruded and granulated at 175-190℃ for 2-3 minutes, and dried to obtain MAH-GMA co-grafted modified PP resin.

7. A high-toughness conductive polypropylene sheet for power batteries according to claim 6, characterized in that, The mass ratio of polypropylene resin, maleic anhydride, glycidyl methacrylate, styrene, and dicumyl peroxide is 100g: 2-4g: 1.5-3g: 0.35-0.75g: 0.2-0.5g.

8. A high-toughness conductive polypropylene sheet for power batteries according to claim 1, characterized in that, The preparation method of the epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid includes the following steps: Under a nitrogen atmosphere, lithium bis(trifluoromethanesulfonyl)imide, reaction solvent, and catalyst were added to a reaction flask and dispersed. The temperature was controlled at 55-60℃, and epichlorohydrin was added for dispersion. The temperature was controlled at 60-70℃ and the reaction was maintained for 3-6 hours. The mixture was then cooled, filtered, evaporated under reduced pressure, and dried to obtain epoxy-functionalized bis(trifluoromethanesulfonyl)imide ionic liquid.

9. A high-toughness conductive polypropylene sheet for power batteries according to claim 8, characterized in that, The reaction solvent consists of anhydrous acetonitrile and anhydrous ethanol in a volume ratio of 4:1; the catalyst consists of anhydrous potassium carbonate and tetrabutylammonium bromide in a mass ratio of 8-15:1-2; the addition ratio of lithium bis(trifluoromethanesulfonylimide), reaction solvent, catalyst, and epichlorohydrin is 100g: 500-800mL: 9-17g: 25-40g.

10. The method for preparing high-toughness conductive polypropylene sheet for power batteries according to any one of claims 1-9, characterized in that, The process includes the following steps: According to the raw material ratio, polypropylene resin, MAH-GMA co-grafted modified PP resin, composite conductive filler, crosslinking penetration enhancer, toughening modifier, compatibilizer, antioxidant, and lubricant are mixed and then added to a twin-screw extruder for melt mixing, extrusion, cooling, and granulation to obtain masterbatch; the masterbatch is dried, extruded and plasticized, calendered / cast, trimmed, and traction-wound to obtain high-toughness conductive polypropylene sheet.

Citation Information

Patent Citations

  • Battery liquid leakage detection device, battery and battery pack

    CN117664462A